Landscape variation in tree regeneration and snag fall drive fuel loads in 24‐year old post‐fire lodgepole pine forests. Issue 8 (22nd November 2016) - Nelson, Kellen N.; Turner, Monica G.; Romme, William H.; Tinker, Daniel B.
Abstract: Escalating wildfire in subalpine forests with stand‐replacing fire regimes is increasing the extent of early‐seral forests throughout the western USA. Post‐fire succession generates the fuel for future fires, but little is known about fuel loads and their variability in young post‐fire stands. We sampled fuel profiles in 24‐year‐old post‐fire lodgepole pine ( Pinus contorta var. latifolia ) stands ( n  =   82) that regenerated from the 1988 Yellowstone Fires to answer three questions. (1) How do canopy and surface fuel loads vary within and among young lodgepole pine stands? (2) How do canopy and surface fuels vary with pre‐ and post‐fire lodgepole pine stand structure and environmental conditions? (3) How have surface fuels changed between eight and 24 years post‐fire? Fuel complexes varied tremendously across the landscape despite having regenerated from the same fires. Available canopy fuel loads and canopy bulk density averaged 8.5 Mg/ha (range 0.0–46.6) and 0.24 kg/m 3 (range: 0.0–2.3), respectively, meeting or exceeding levels in mature lodgepole pine forests. Total surface‐fuel loads averaged 123 Mg/ha (range: 43–207), and 88% was in the 1, 000‐h fuel class. Litter, 1‐h, and 10‐h surface fuel loads were lower than reported for mature lodgepole pine forests, and 1, 000‐h fuel loads were similar or greater. Among‐plot variation was greater in canopy fuels than surface fuels, and within‐plot variation was greater than among‐plot variation for nearly all fuels. Post‐fire lodgepole pine density was the strongest positive predictor of canopy and fine surface fuel loads. Pre‐fire successional stage was the best predictor of 100‐h and 1, 000‐h fuel loads in the post‐fire stands and strongly influenced the size and proportion of sound logs (greater when late successional stands had burned) and rotten logs (greater when early successional stands had burned). Our data suggest that 76% of the young post‐fire lodgepole pine forests have 1, 000‐h fuel loads that exceed levels associated with high‐severity surface fire potential, and 63% exceed levels associated with active crown fire potential. Fire rotations in Yellowstone National Park are predicted to shorten to a few decades and this prediction cannot be ruled out by a lack of fuels to carry repeated fires.